Irreversible Acquired Noncompaction Cardiomyopathy in a Parturient with Corrected Atrial Septal Defect: A Case Report and Clinical Implications. (29th February 2020) - Al-Aamri, Is'haq; Derzi, Simone; Moore, Albert; Bottega, Natalie; Ordoñez, Maria V.; Villeneuve, Valerie; Hatzakorzian, Roupen
Abstract : Left ventricular noncompaction (LVNC) is described as a cardiomyopathy with an increase in left ventricle trabeculations and recesses. We report a rare case of persistent pregnancy-acquired LVNC cardiomyopathy and review the anesthetic peripartum management strategies. A 33-year-old parturient was followed closely by the high-risk obstetric service for her second pregnancy. She had an unresolved LVNC cardiomyopathy that was diagnosed during her first pregnancy for which she had a caesarean section. Her symptoms included occasional palpitations and dyspnea. She was started on metoprolol and enoxaparin. A successful caesarean section was performed at 37 weeks gestation under regional anesthesia. Echocardiograms prior to and during the second pregnancy demonstrated persistence of the LV hypertrabeculations, LV systolic dysfunction, and a left ventricular ejection fraction (LVEF) of 35%. Pregnancy-induced LV hypertrabeculations occur in a significant proportion of women, but most cases spontaneously resolve completely. Favorable maternal and fetal outcomes require multidisciplinary care and careful selection of the anesthetic technique and drugs that maintain stable hemodynamics.